Normative Measurement of Orbital Structures in Computed Tomography - Rokka, Damodar; Poudel, Sharma; Kayastha, Prakash; Suwal, Sundar; Poudyal, Sudil; Chhetry, Saroj; Shrestha, Shantalall; Karn, Rakesh (Journal of Institute of Medicine Nepal, 2020)
Introduction Normal orbital dimensions are important for diagnosing orbital pathologies. Computed tomography (CT) of the orbit is an important modality offering high accuracy for precise measurements of orbit. The study was disbursed to ascertain criteria for the normative values of the various orbital dimensions using computed tomography in patients visiting Tribhuvan University Teaching Hospital, Kathmandu. Methods Orbital volume, ocular diameter, length of the interzygomatic line (IZL), the distance of the posterior extent of the globe from the interzygomatic line, globe position, diameters of extraocular muscles (medial, lateral, superior group, and inferior rectus) and lens density were measured in each eye of 172 patients undergoing CT examination of paranasal sinuses. The correlations with age and sex were also analyzed. Results Mean values (mean±SD) of orbital volume, ocular diameter, IZL, globe position and lens density were 24.54±2.57 cm3, 2.44±0.22 cm, 94.3±6.2 mm, 12.3±2.4 mm and 141.43±16.62 HU respectively. Mean diameters of extraocular muscles were 3.67± 0.52 mm, 3.36± 0.50 mm, 3.74±0.42 mm and 3.87±0.38 mm for medial rectus, lateral rectus, inferior rectus and the superior group respectively. There was no significant age and gender difference in most of the measurements. There was significant positive correlation of age with lens density, orbital volume and ocular diameter (p<0.05). Conclusion Normative data of different orbital measurements were obtained. The present result may help radiologists and ophthalmologists to accurately assess various orbital parameters, particularly in Nepalese populations.